Observation of magnetic anomalies in one-step solvothermally synthesized nickel-cobalt ferrite nanoparticles - Datt, Gopal; Sen Bishwas, Mousumi; Raja, M. Manivel; Abhyankar, A. C. (Nanoscale, 2016)
Magnetic anomalies corresponding to the Verwey transition and reorientation of anisotropic vacancies are observed at 151 K and 306 K, respectively, in NiCoFe2O4 nanoparticles (NPs) synthesized by a modified-solvothermal method followed by annealing. Cationic disorder and spherical shape induced non-stoichiometry suppress the Verwey transition in the as-synthesized NPs. On the other hand, reorientation of anisotropic vacancies is quite robust. XRD and electron microscopy investigations confirm a single phase spinel structure and the surface morphology of the as-synthesized NPs changes from spherical to octahedral upon annealing. Rietveld analysis reveals that the Ni2+ ions migrate from tetrahedral (A) to octahedral (B) sites upon annealing. The Mossbauer results show canted spins in both the NPs and the strength of superexchange is stronger in Co-O-Fe than Ni-O-Fe. Magnetic force images show that the as-synthesised NPs are single-domain whereas the annealed NPs are multi-domain octahedral particles. The FMR study reveals that both the NPs have a broad FMR line-width; and resonance properties are consistent with the random anisotropy model. The broad inhomogeneous FMR line-width, observation of the Verwey transition, tuning of the magnetic domain structure as well as the magnetic properties suggest that the NiCoFe2O4 ferrite NPs may be promising for future generation spintronics, magneto-electronics, and ultra-high-density recording media as well as for radar absorbing applications.

New insights towards strikingly improved room temperature ethanol sensing properties of p-type Ce-doped SnO2 sensors - Kumar, Manjeet; Bhatt, Vishwa; Abhyankar, A. C.; Kim, Joondong; Kumar, Akshay; Patil, Sagar H.; Yun, Ju-Hyung (Scientific Reports, 2018)
In this article, room temperature ethanol sensing behavior of p-type Ce doped SnO2 nanostructures are investigated successfully. Interestingly, it is examined that the abnormal n to p-type transition behavior is caused by Ce doping in SnO2 lattice. In p-type Ce doped SnO2, Ce ion substituting the Sn is in favor of generating excess holes as oxygen vacancies, which is associated with the improved sensing performance. Although, p-type SnO2 is one of the important materials for practical applications, it is less studied as compared to n-type SnO2. Pure and Ce doped SnO2 nanostructures were successfully synthesized by chemical co-precipitation method. The structure, surface morphology, unpaired electrons (such as free radicals), and chemical composition of obtained nanoparticleswere studied by various kinds of characterization techniques. The 9% Ce doped SnO2 sensors exhibit maximum sensor response of similar to 382 for 400 ppm of ethanol exposure with fast response time of similar to 5 to 25 sec respectively. Moreover, it is quite interesting that such enhancement of ethanol sensing is unveiled at room temperature, which plays a key role in the quest for better ethanol sensors. These remarkably improved sensing results are attributed to uniformly distributed nanoparticles, lattice strain, complex defect chemistry and presence of large number of unpaired electrons on the surface.